Radiography and abdominal CT compared with sacroiliac joint CT in the diagnosis of sacroiliitis. (October 2017) - Melchior, Julian; Azraq, Yusef; Chary-Valckenaere, Isabelle; Rat, Anne-Christine; Texeira, Pedro; Blum, Alain; Loeuille, Damien
Background: The presence of structural sacroiliitis is strong evidence for the diagnosis of spondyloarthritis (SpA). Purpose: To assess the performance of abdominal computed tomography (CT) and pelvic plain radiography for the diagnosis of structural sacroiliitis compared with sacroiliac CT (SI joint CT) considered the reference technique in patients with SpA. Material and Methods: All SpA patients eligible for biologic treatment were selected from 2005 to 2012. An assessment of sacroiliitis was based on radiography according to the modified New York criteria and on abdominal CT and SI joint CT scans depending on the presence of erosion on at least two consecutive slices. A senior rheumatologist and radiologist independently scored the grade and diagnosis of structural sacroiliitis for the three imaging modalities. After a consensus reading of conflicting examinations (radiography and CT), a final diagnosis of structural sacroiliitis was attained. Results: Of the 72 patients selected, sacroiliitis was diagnosed on radiography, abdominal CT, and SI joint CT in 40, 31, and 44 patients, respectively. Inter-reader agreements for the grade of sacroiliitis were substantial for the three imaging modalities, with a weighted kappa range of 0.63–0.75 (95% confidence interval [CI], 0.52–0.83), and they were moderate for the diagnosis of sacroiliitis, with a kappa range of 0.50–0.55 (95% CI, 0.32–0.74). The sensitivity and specificity were 79.1% and 70.5%, respectively, for radiography and 82.1% and 100%, respectively, for abdominal CT. Conclusion: This study demonstrates the relevance of abdominal CT for the diagnosis of structural sacroiliitis, with good sensitivity and excellent specificity. These imaging techniques avoid unnecessary examinations.